Influence of pedaling technique on metabolic efficiency in elite cyclists - Cámara, J.; Maldonado-Martin, S.; Artetxe-Gezuraga, X.; Vanicek, N. (Biology of Sport, 2012)
Our objective was to investigate the influence of pedaling technique on gross efficiency (GE) at various exercise intensities in twelve elite cyclists ( VO2max=75.7 ± 6.2 ml/kg/min). Each cyclist completed a VO2max assessment, skinfold measurements, and an incremental test to determine their lactate threshold (LT) and onset of blood lactate accumulation (OBLA) values. The GE was determined during a three-phase incremental exercise test (below LT, at LT, and at OBLA). We did not find a significant relationship between pedaling technique and GE just below the LT. However, at the LT, there was a significant correlation between GE and mean torque and evenness of torque distribution (r=0.65 and r=0.66, respectively; p < 0.05). At OBLA, as the cadence frequency increased, the GE declined (r=-0.81, p < 0.05). These results suggest that exercise intensity plays an important role in the relationship between pedaling technique and GE.